High Order Accurate Approximation of the First and Pure Second Derivatives of the Laplace Equation on a Rectangle and a Rectangular Parallelepiped - Sadeghi, Hamid Mir Mohammad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
In thisthesis,wediscusstheapproximationofthefirstandpuresecondorderderiva- tivesforthesolutionoftheDirichletproblemforLaplace’sequationonarectangular domain andinarectangularparallelepiped.Inthecasewhenthedomainisarectangle, the boundaryvaluesonthesidesoftherectanglearesupposedtohavesixthderivatives satisfying theHöldercondition.Onthevertices,besidesthecontinuity,thecompat- ibility conditions,whichresultfromtheLaplaceequation,forthesecondandfourth derivativesoftheboundaryfunctions,givenontheadjacentsides,arealsosatisfied. Under theseconditionsauniformapproximationoforder O 􀀀 h4 (h is thegridsize),is obtained forthesolutionoftheDirichletproblemonasquaregrid,itsfirstandpure second derivatives,byasimpledifferenceschemes. In thecasearectangularparallelepiped,weproposeandjustifydifferenceschemes for thefirstandpuresecondderivativesapproximationofthesolutionoftheDirichlet problem for3DLaplace’sequtation.Theboundaryvaluesonthefacesoftheparal- lelepiped areassumedtohavethesixthderivativessatisfyingtheHöldercondition. Theyarecontinuousontheedges,andtheirsecondandfourthorderderivativessatisfy the compatibilityconditionswhichresultsfromtheLaplaceequation.Itisprovedthat the solutionsoftheproposeddifferenceschemesconvergeuniformlyonthecubicgrid with order O(h4), where h is thegridstep.Forbothcasesnumericalexperimentsare demonstrated tosupporttheanalysismade. Keywords: Finite differencemethod,approximationofderivatives,uniformerror, Laplace equation.

ÖZ : Bu tezde,LaplaceDenkleminindikdörtgenselbölgedevedikdörtgenlerprizmasıüz- erinde Dirichletproblemininçözümüiçinbirincimertebedenvepürikincimertebeden türevlerininyakla¸sımıtartı¸sılır.Tanımbölgesinindikdörtgenoldu˘gu durumdadikdört- genin kenarlarındaverilensınırfonksiyonlarınınaltıncıtürevlerininHölder¸sartını sa˘gladıkları kabuledildi.Kö¸selerdesüreklilik¸sartınınyanındaLaplacedenkleminden sonuçlanan kö¸selerinkom¸sukenarlarındaverilensınırde˘ger fonksiyonlarınınikinci vedördüncütürevleriicinuyumluluk¸sartlarıdasa˘glandı. Bu¸sartlaraltındaDirich- let problemininkareızgaraüzerindeçözümüiçinveçözümünbirincivepürikinci türevleriiçin O(h4) (h adım uzunlu˘gu) düzgünyakla¸sımısadebirfark¸semasıileelde edildi. ˙Ikinci durumdatanımbölgesidikdörtgenlerprizmasıoldu˘gunda Laplacedenkleminin Dirichlet problemininçözümününbirincivepürikincitürevlerininyakla¸sımıiçinfark ¸semalarıönerilirvesa˘glanır.Prizmanınyüzeylerindeverilensınırde˘gerlerinin altıncı türevlerininHölderko¸sulunusa˘gladı˘gı kabuledildi.Kö¸selerdesüreklidirlerveonların ikinci vedördüncümertebedentürevleriLaplacedenklemlerindensonuçlananuyum- luluk ko¸sulunusa˘glar.Önerilenfark¸semalarınınçözümününküpızgaralarüzerindeh ızgarauzunlu˘gu oldu˘gunda O(h4) mertebesinden düzgünyakınsadı˘gı ispatlandı.Her iki durumiçinsayısalörnekleryapılananalizleridesteklemekiçinverildi. Anahtar Kelimeler: Sonlu farkmetodu,türevlerinyaklasımı,düzgünhata,Laplace denklemi.
Doctor of Philosophy in Applied Mathematics and Computer Science. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2016. Supervisor: Prof. Dr. Adıgüzel Dosiyev.
Keywords: Mathematics; Applied Mathematics and Computer Science; Laplace Functions - Mathematics; Finite differencemethod; approximationofderivatives; uniformerror; Laplace equation